2004
DOI: 10.1073/pnas.0401196101
|View full text |Cite
|
Sign up to set email alerts
|

Specialization of primary auditory cortex processing by sound exposure in the “critical period”

Abstract: Environmental acoustic exposure to a complex tone sequence within the critical period in infant rats resulted in the emergence of large-scale, selective changes that radically altered primary auditory cortex (A1) organization. In the sound exposure-revised A1, responses were segregated into two explicit zones representing spectrally and temporally separated lower and higher frequency tone sequence progressions. Cortical neurons between these two A1 zones were poorly driven by sound stimuli. Stimulus sequence-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 25 publications
3
57
0
1
Order By: Relevance
“…Our findings of auditory brain plasticity before full gestation are in keeping with several studies, primarily by Merzenich and colleagues, showing that early auditory experience, either in the form of enrichment or impoverishment, can have a substantial impact on both the structural and functional development of the AC in rat pups (26,27,29,31,57,58). Similarly, an established body of work by Lickliter and colleagues has shown that bobwhite quail chicks receiving auditory stimulation early in embryogenesis demonstrated improved auditory learning and memory when tested postnatally (59)(60)(61).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of auditory brain plasticity before full gestation are in keeping with several studies, primarily by Merzenich and colleagues, showing that early auditory experience, either in the form of enrichment or impoverishment, can have a substantial impact on both the structural and functional development of the AC in rat pups (26,27,29,31,57,58). Similarly, an established body of work by Lickliter and colleagues has shown that bobwhite quail chicks receiving auditory stimulation early in embryogenesis demonstrated improved auditory learning and memory when tested postnatally (59)(60)(61).…”
Section: Discussionsupporting
confidence: 91%
“…Nakahara et al (19) exposed infant rats to sound sequences within the critical period and showed that this exposure resulted in enduring sequence-specific activation of neurons recorded all across a broad cortical area representing sequence frequencies. Kilgard and Merzenich (5) paired sound sequences with electrical stimulation of the nucleus basalis in adult rats and showed that this pairing resulted in emergent sequencespecific responses that amplified the responses of later stimulus components of conditioned stimulus sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The auditory response of AC neurons can be modulated by stimulus sequence (McKenna et al 1989;Brosch et al 1999;Brosch and Schreiner 2000), and some AC neurons respond selectively to a particular sequential combination of sounds (Suga et al 1978;Kilgard and Merzenich 2002;Nakahara et al 2004). These studies suggest that sound sequences can be coded by AC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the auditory cortex (AC) in sound sequence discrimination has been suggested by various studies. AC neurons respond selectively to a particular sequence of sounds (Suga et al 1978;Kilgard and Merzenich 2002;Nakahara et al 2004). The auditory response of AC neurons can be either enhanced or inhibited by preceding sounds (McKenna et al 1989;Brosch et al 1999;Brosch and Schreiner 2000).…”
mentioning
confidence: 99%